(untitled) (Med Phoenix, 2023)
Introduction: Root canal treatment (RCT) for permanent teeth involves the use of biologically acceptable chemical and mechanical treatment of the root canal system to promote healing and repair of the peri radicular tissues. The aim of the study was to analyze the reasons and pattern of demand for root canal treatment among patients attending a tertiary care center of Madhesh Province, Nepal. Materials and Methods: This was a descriptive cross-sectional study of patients who received root canal treatment in the Department of Conservative Dentistry and Endodontics, National Medical College, Birgunj, Nepal between September 2022 and February 2023.The demographic and clinical data of patients were recorded and statistical analysis was performed using SPSS version 24. Association between the variables was analyzed by Fischer exact tests. P-value<0.05 was considered as statistically significant. Results: 206 patients who received root canal treatment participated in this study. More mandibular teeth (53.9%) were root-treated compared to maxillary teeth (46.1%). The first molars constituted the most prevalent root-treated teeth (43.7%), followed by the second molars (26.7%) and the central incisors (10.7%). The most common chief complaint was pain (66%) and caries (75.7%) was the most frequently encountered pathology. The association of age category and dental arch with the type of root-treated teeth was statistically significant (p < 0.001 and p <0.004 respectively). Conclusion: Irreversible pulpitis caused by caries was the predominant indication for root canal treatment, with pain being the most common presenting complaint. The demand for treatment was higher in females and among patients within 21-40 years age category. More teeth from the mandibular arch were root-treated while the first molar was the most frequently treated tooth.